An investigation of the contribution of Single Photon Emission Computed Tomography to the diagnosis of skeletal metastases using bone scan in the African context - Elmadani, Ahmed Elkhidir (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.